Menyerang Kehormatan atau Harkat dan Martabat Presiden: Urgensi Pengaturan Vis-a-Vis Kebebasan Berekspresi dan Kebebasan Pers - Prianter Jaya Hairi (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2022)
The articles regulation in the Bill of the Criminal Code regarding acts of attacking the honor and dignity of the president has been criticized. Some articles are considered to have the potential to threaten the right to freedom of expression and freedom of the press, which are part of the human rights guaranteed by the Constitution. On the other hand, legislators also have a raison d’etre as the urgency of regulation. This study aims to explore in depth the significance of the substantial regulation of the articles, as well as to examine some potential conflicts with the right to freedom of expression and freedom of the press. This study is a type of normative legal research, with data analysis methods carried out with a qualitative approach to secondary data. The results of the analysis show that the articles concerning acts attacking the honor and dignity of the president or vice president still needed/urgent to be re-formulate in the Bill of the Criminal Code. However, it should be noted that it is necessary to adjust some of the explanations of the articles. In addition, the general construction of these articles cannot be said to have violated human rights principles related to the right to freedom of expression and freedom of the press. However, there should be an assurance that protecting the freedom of expression and freedom of the press still needs to be emphasized in the Bill of the Criminal Code. So far, the reality shows that there are still poor implementations in law enforcement related to some articles, such as articles on contempt. AbstrakPengaturan pasal di RUU KUHP terkait perbuatan menyerang kehormatan atau harkat dan martabat presiden mendapat kritik. Pasal tersebut dinilai berpotensi mengancam hak atas kebebasan berpendapat dan kebebasan pers yang merupakan bagian dari hak asasi manusia yang dijamin oleh Konstitusi. Di sisi lain, pembentuk undang-undang juga memiliki raison d’etre yang merupakan urgensi pengaturan pasal. Artikel ini bertujuan untuk mengupas secara mendalam arti penting dari pengaturan substansi pasal tersebut, sekaligus mengkaji bagaimana potensi persinggungan dengan hak atas kebebasan berpendapat dan kebebasan pers. Kajian ini merupakan jenis penelitian hukum normatif, dengan metode analisis data yang dilakukan dengan pendekatan kualitatif terhadap data sekunder. Hasil analisis menunjukkan bahwa pasal mengenai perbuatan penyerangan harkat dan martabat presiden atau wakil presiden masih tetap diperlukan/urgen untuk diatur kembali dalam RUU KUHP. Namun dengan catatan, perlu penyesuaian terhadap beberapa penjelasan pasal. Selain itu, bahwa secara umum, konstruksi pasal-pasal tersebut tidak dapat dikatakan telah menyalahi prinsip-prinsip HAM terkait hak atas kebebasan berekspresi dan kebebasan pers. Namun demikian, jaminan perlindungan kebebasan berekspresi dan kebebasan pers masih tetap perlu dipertegas dalam RUU KUHP. Karena kenyataan di lapangan selama ini, menunjukkan masih ada terjadi salah penerapan dalam penegakan hukum terkait pasal-pasal sejenis pasal penghinaan.